2017
DOI: 10.1080/03601234.2017.1330069
|View full text |Cite
|
Sign up to set email alerts
|

Transport of oxytetracycline, chlortetracycline, and ivermectin in surface runoff from irrigated pasture

Abstract: The transport of oxytetracycline, chlortetracycline, and ivermectin from manure was assessed via surface runoff on irrigated pasture. Surface runoff plots in the Sierra Foothills of Northern California were used to evaluate the effects of irrigation water application rates, pharmaceutical application conditions, vegetative cover, and vegetative filter strip length on the pharmaceutical discharge in surface runoff. Experiments were designed to permit the maximum potential transport of pharmaceuticals to surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…2016; Bair et al, 2017;Li et al, 2016;Popova et al, 2013). LCM is highly soluble and has been detected in leachate (Domínguez et al, 2014), surface water , and snowmelt runoff from manure-amended soil.…”
Section: Ctcmentioning
confidence: 99%
“…2016; Bair et al, 2017;Li et al, 2016;Popova et al, 2013). LCM is highly soluble and has been detected in leachate (Domínguez et al, 2014), surface water , and snowmelt runoff from manure-amended soil.…”
Section: Ctcmentioning
confidence: 99%
“…In the literature, there are only a few studies investigating the fate and transport of veterinary antibiotics from cattle grazing areas to surface runoff. For instance, in a study conducted by Bair et al (2017), the occurrence of chlortetracyline and oxytetracycline in surface waters affected by irrigated pasture was investigated. They reported that the concentration ranges of chlortetracycline and oxytetracycline were 0.001-0.7 and 0.001-1.3 μg/L, respectively.…”
Section: Field Samples Analysismentioning
confidence: 99%
“…As such, a full understanding of VA transport and fate in soil is of high relevancy with respect to their environmental risk in manured farmland. Dominant paths of VA transport in farmland soil are runoff and leaching, both of which are dependent on VA sorption to soil, soil hydraulic properties, and precipitation characteristics [14][15][16][17]. It is worth noting that the sorption of VAs to the soil matrix can not only reduce their mobility and availability, but also protect antibiotics from degradation [18].…”
Section: Introductionmentioning
confidence: 99%